2011
DOI: 10.1371/journal.pone.0026431
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatic Analysis of Pathogenic Missense Mutations of Activin Receptor Like Kinase 1 Ectodomain

Abstract: Activin A receptor, type II-like kinase 1 (also called ALK1), is a serine-threonine kinase predominantly expressed on endothelial cells surface. Mutations in its ACVRL1 encoding gene (12q11-14) cause type 2 Hereditary Haemorrhagic Telangiectasia (HHT2), an autosomal dominant multisystem vascular dysplasia. The study of the structural effects of mutations is crucial to understand their pathogenic mechanism. However, while an X-ray structure of ALK1 intracellular domain has recently become available (PDB ID: 3MY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 105 publications
1
7
0
Order By: Relevance
“…7A). Consistent with previous predictions, mutations that map to the highly conserved cysteine residues disrupt the core intramolecular disulfide bonds (33,34). We found that only three mutations (H66P, G79R, and H87D) directly affect residues at the BMP9 interface.…”
supporting
confidence: 91%
“…7A). Consistent with previous predictions, mutations that map to the highly conserved cysteine residues disrupt the core intramolecular disulfide bonds (33,34). We found that only three mutations (H66P, G79R, and H87D) directly affect residues at the BMP9 interface.…”
supporting
confidence: 91%
“…In a model of the ALK1, the structure of this region was predicted to contain several residues involved in the ALK1/ BMP9 interaction (35).…”
Section: Discussionmentioning
confidence: 99%
“…Both patients carry ACVRL1 mutations in exon 3, an in-frame deletion (p. l55_V56del), and a missense mutation (p. C51Y). The missense mutation was included in the paper by Scotti et al 28 and was among the mutations with the higher destabilizing effects on protein structure. The presence of hepatic AVMs fits with its increased frequency in females carrying ACVRL1 mutations; 13 both cases are younger than those more severely affected, and, currently, younger age is likely a better explanation for their mild GI presentation of the disease than the presence of a peculiar mutation.…”
Section: Other Clinical Manifestationsmentioning
confidence: 99%